Políticas públicas de fomento de la economía social y solidaria en la ciudad de Montreal - Marguerite Mendell; Nancy Neamtan; Hyuna Yi (United Nations Research Institute for Social Development (UNRISD), 2020)
An enabling environment for the social and solidarity economy (SSE) largely depends on policy co-construction with stakeholders, and their commitment to implement policy across all levels of government, especially at the local level. The city of Durban is emerging as an exemplar for creating an enabling environment for the SSE to flourish through the co-construction process of policy making with relevant stakeholders and the implementation of these policies in a consultation process. Through the eThekwini Metropolitan Municipality (eTMM)1 in the province of KwaZulu-Natal (KZN), the city experienced success in establishing an enabling SSE environment by means of its Cooperative Development Plan (CDP). Together with partners and stakeholders2, the CDP delivered a model that serves as a tried and tested example to be replicated all over South Africa. Following various socio-economic challenges, the country experienced a proliferation of SSE entities, and active3 registered SSE entities now represent between 16% and 18% of the total of all active registered enterprise entities of all sectors of South Africa. Within the national SSE landscape, the KZN province is a stronghold, accommodating 32% of all registered cooperatives and an estimated 20% of non-profit organizations (NPO) including social enterprises in South Africa.
Keywords: 330; Sozialwirtschaft; Stakeholder; Politische Entscheidung; Durban; Südafrika